Constructing Power Architecturally: A Spatial Look At Uniate Catholicism In Kyiv Today - Mueller II, Alfred (Ethnologies, 2002)
RésuméThis essay explores the Uniate Catholic Church of Ukraine and its recent successes in resource allocation in the capital city of Kyiv. Positing that the social use of space allows a people to negotiate the geographies of power that surround them, this article argues that, in excavating the ideology inscribed in their architectural style and spatial appropriations, we come to understand the ways in which the Uniate community in Kyiv is articulating a unique post-Soviet identity.